Analysis of a mechanism to evaluate upper limb muscle activity based on surface electromyography using the Myo-EMG device - Auccahuasi, W. (2019)
When we want to work with signals produced by the human body, we face different challenges that we must address, from the sensor to be used, through the conditioning of the signal for later registration and analysis, these stages are important to have a Good record of the clean interference signal that are foreign to the signal. One of the challenges you have when working with the electromyography signal, is to be able to understand the behavior of the muscles accompanied by the biophysics of the movement that is performed, for your better understanding and analysis the monitoring of several muscles at the same time is required, what originates a multichannel record, this condition is a complex requirement at the time of being able to design a team that can perform this multi record, being able to record these signals is vital for a subsequent analysis and understanding of muscle activity. This paper presents the use of a mechanism that allows us to simultaneously record 8 electromyography signals, based on the use of the MYO EMG device, which is used in many applications such as wireless control through the movement of the Upper limbs is also used in measuring the level of activity of muscle mass, the proposal presented is characterized by recording the muscle activity of 8 muscles of the upper limb simultaneously and its subsequent visualization for analysis, signals they are presented simultaneously, for the evaluation of the proposal the study was carried out on three patients with problems in the upper extremities, the result is presented by the graphs of the 8 muscles analyzed to each patient.